Efficacy of different cerclage suture materials in reducing preterm birth. (17th October 2020) - Stafford, Irene A.; Kopkin, Rachel H.; Berra, Alexandra L.; Daigle, Patrick; Bergeron, Michelle; Karlin, Samantha; Hodge, Kimberly; Hagan, Joseph L.
Abstract: Objective: To compare the efficacy of monofilament suture, braided polyester thread, and 5 mm tape suture in reducing preterm birth (PTB). Study design: Women who received a cerclage at Touro Infirmary, New Orleans, LA, USA, between 1 January, 2011 and 31 December, 2016 were identified using ICD-9/10 codes. All charts were reviewed for demographic and obstetrical variables including gestational age (GA) at delivery. Results: Of 145 women who received a cerclage, 36 were excluded due to incomplete charts leaving 109 for analysis. There was no significant difference in gestational age at cerclage placement or delivery among women with monofilament, braided, or 5 mm tape cerclages ( p = .936 and p = .919, respectively) nor was there a difference in the proportion who delivered at ≥32, 34, or 37 weeks across groups with differing cerclage material ( p = .270, p = .275, and p = .419, respectively). There was no difference in GA at delivery for patients who received 17-OHP compared to those who did not ( p = .362). There were also no differences with respect to birth outcomes such as birthweight ( p = .938), Apgar scores ( p = .477, p = .430) or neonatal intensive care admission rates (NICU) ( p = .304). Analysis revealed no difference in characteristics between groups including history of PTB or indication for removal ( p = .371, p = .317). Conclusion: We found no difference in pregnancy prolongation when comparing different suture material used for indicated cerclages. We also found no differences with respect to rates of maternal infection or adverse neonatal outcomes among groups. Rationale This study was conducted to evaluate the efficacy of different suture materials in increasing gestational age at delivery and reducing preterm birth.